Effects of the particle morphology and volume fraction of coarse aggregate on the mechanical properties of concrete - Zhao, Wei; Si, Zheng; Du, Xiaoqi; Huang, Lingzhi (Frontiers in Materials, 2023)
The morphology and volume fraction of coarse aggregate particles significantly influence the mechanical characteristics of concrete. This paper presents the development of a numerical model for pebble concrete by combining experiments with the discrete element method.The mesoscopic parameters between mortars and the contact surface between mortars and aggregates in the model were calibrated by comparing simulated stress-strain relationships with experimental data from pebble concrete. Subsequently, the model and mesoscopic parameters were validated by comparing them with the experimental results. The obtained mesoscopic parameters were then utilized in the numerical modeling of uniaxial compression for single-shaped coarse aggregate concrete. Results showed that the peak stress of elliptical aggregate concrete was 2.8 MPa higher than that of oblate spherical aggregate concrete, leading to more cracks and severe damage in the former. Thus, elliptical aggregates proved more suitable as coarse aggregates for concrete than oblate spherical aggregates. Furthermore, the study investigated the influence of ellipsoidal aggregate volume fraction on concrete strength. The compressive strength reached the highest when the volume fraction of ellipsoidal aggregate was 57%. Therefore, the ideal coarse aggregate volume fraction was determined to be 57%. These results offer valuable insights into designing concrete mix proportions.